Prognostic Factors and Long-Term Outcome Prediction in Patients with Hypopharyngeal Carcinoma Treated with (Chemo)radiotherapy: Development of a Prognostic Model - Pala, Miloslav; Novakova, Pavla; Tesar, Adam; Vesela, Lucie; Vrana, Antonin; Sukova, Jarmila; Pechacova, Zdenka; Holeckova, Petra; Drbohlavova, Tereza; Podlesak, Tomas; Tesarova, Petra (Biomedicines, 2025)
Background/Objectives: To evaluate the effectiveness of curative (chemo)radiotherapy in patients with hypopharyngeal carcinoma and to identify prognostic factors influencing treatment outcomes. Methods: We conducted a retrospective study of 173 consecutive patients, treated with definitive or postoperative (chemo)radiotherapy from 2002 to 2020 [median age 60 years; current/former smokers 95%; UICC stage III/IV 96%]. Radiation therapy was preceded by a radical resection of a primary tumor in 32% of patients. One hundred patients received chemotherapy. Results: The median total dose of radiotherapy achieved was 70 Gy. The five- and ten-year locoregional controls were 63%, and the five- and ten-year distant controls were 77% and 76%, respectively. The five- and ten-year overall survival rates were 24% and 9%, respectively. Conclusions: The results demonstrate the limited effectiveness of curative (chemo)radiotherapy in patients with hypopharyngeal carcinoma with long-term locoregional and distant control of half of the treated patients. The multivariate analysis indicated that initial surgery, chemotherapy, comorbidity score (as assessed by ACE-27), pretreatment tracheostomy, hemoglobin level and initial response to treatment were the strongest prognostic factors in predicting survival. Using these factors, corresponding predictive models were constructed.
Keywords: predictive model; hypopharyngeal carcinoma; curative radiotherapy; prognostic factors; chemoradiotherapy